Social Media and Political Communication in the 2023 Campaign in Nigeria - Mmesomachukwu Chukwuemeka Iloh; Ekpali Joseph Saint; Abdullahi Aliyu Maiwada; Timothy Ekeledirichukwu Onyejelem (Budapest International Research and Critics University, 2026)
This paper examines the role of social media in shaping political communication during the 2023 general election campaign in Nigeria. It investigates how political actors, parties, and citizen networks used digital platforms to disseminate messages, mobilise supporters, counter opposition narratives, and influence public opinion. Secondary data was used to generate relevant information on social media platform like Facebook, Twitter, Instagram, TikTok, and WhatsApp, to identify communication patterns, strategies, and audience engagement behaviour. The paper argues that social media served as a critical arena for agenda-setting, political persuasion, real-time interaction, and participatory discourse, while also amplifying misinformation, emotional appeals, and polarising content. The paper concludes that social media significantly reshaped Nigeria’s 2023 campaign landscape by expanding political reach, enhancing youth participation, and redefining how political messages are produced, circulated, and contested. Nigerian political candidates have endeavoured to navigate the complex social media landscape. Initiatives such as fact-checking organisations and partnerships with digital influencers came as countermeasures to misinformation and targeted messaging.